Analysis of the most demanding passages of play in elite youth soccer: a comparison between congested and non-congested fixture schedules - Jimenez, S. L.; Mateus, N.; Weldon, A.; Bustamante-Sanchez, A.; Kelly, A. L.; Sampaio, J. (Science and Medicine in Football, 2023)
This study aimed to examine the most demanding passages of play in elite youth soccer for congested and non-congested fixture schedules. Seventeen elite youth male soccer players (18.2 ± 1.3 years old) participated in this study across 30 competitive matches. Assessed matches included congested (n = 12, three matches within eight consecutive days or less) and non-congested matches (n = 18, at least 5 days between matches). The players` activity profiles during matches were analysed using global positioning measurement units (GPS). Players activity included: distance covered, distance covered at different velocities, high-intensity accelerations and decelerations, and player load. The most demanding passages (MDP) of match play was calculated using a moving average method within three-time windows (i.e., 1, 5, and 10 min). Data were analysed using a Bayesian ANOVA. During congested fixtures, the players` distance covered and player load declined, with the former decreasing across all the MDP time windows, whereas the latter exclusively into the long-time windows (i.e., 5 and 10 min). Conversely, statistical differences in the remaining variables were anecdotal and in favour of the null hypothesis (i.e., Bayes factor <1), suggesting a non-influence of the competition fixture schedule. These findings provide insight into the MDP of youth soccer, helping practitioners to periodize training and recovery strategies during different competitive fixture schedules.